Partisipasi Dan Keaktifan Berdiskusi Peserta Didik Dalam Pembelajaran Biologi Kelas VIII SMP Negeri Oenenu (JBIOEDRA: Jurnal Pendidikan Biologi, 2024)
The problem in this research lies in the teaching of biology at SMPN Oenenu, where many students are less actively involved in the learning process. This is because the teaching process at the school is still conducted using conventional methods, such as lectures and question-and-answer sessions. The purpose of this study is to determine the participation and activeness of students in discussions during biology lessons in class VIII at SMP Negeri Oenenu. The population of this study includes all class VIII students at SMP Negeri Oenenu for the 2022-2023 academic year, with a sample of 20 students from one class, namely class VIIIA. The method used is descriptive quantitative, with data collection techniques in the form of observation sheets consisting of 12 items. The results of the study show that students demonstrated participation and activeness during discussion activities in the learning process. This is evident from the analysis of respondents’ results, which showed an average score of 73.33% for participation and 75.62% for activeness indicators. Thus, the participation and activeness of class VIII students at SMP Negeri Oenenu are categorized as good. The conclusion of this study is that the class VIII students at SMPN Oenenu participate and are active in biology learning.
Keywords: Biology learning, Discussion activeness, Junior high school. Participation, Students.